2017
DOI: 10.4103/1008-682x.169563
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic and nonapoptotic function of caspase 7 in spermatogenesis

Abstract: Recent studies have reported that caspase 7 has an apoptotic and nonapoptotic function. However, the relationship between caspase 7 and spermatogenesis remains unknown. This study aimed to investigate the possible function of caspase 7 during normal and abnormal spermatogenesis. The cleaved form of caspase 7 was detected in testis tissues at different postpartum times (5–14 weeks) by qRT-PCR, Western blot and immunohistochemistry (IHC). Then, the mice models of spermatogenic dysfunction were obtained by busulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Caspase 7 was major mainly in spermatogenic cells and have apoptotic function in spermatogenic dysfunction. 27 In the current study, we found that LBP could reverse DDP-induced caspase 3, caspase 7, and caspase 12 upregulation. In addition, the formation of autophagic vacuoles was detected using immunohistochemistry and MDC staining.…”
Section: Discussionsupporting
confidence: 51%
“…Caspase 7 was major mainly in spermatogenic cells and have apoptotic function in spermatogenic dysfunction. 27 In the current study, we found that LBP could reverse DDP-induced caspase 3, caspase 7, and caspase 12 upregulation. In addition, the formation of autophagic vacuoles was detected using immunohistochemistry and MDC staining.…”
Section: Discussionsupporting
confidence: 51%
“…Such activation has been previously reported in lung cancer-derived cell lines [55]. Interestingly, recent studies demonstrated that caspases can exert both apoptotic and non-apoptotic activities, and their activation does not exclusively lead to cell death [56][57][58]. Indeed, caspases are involved in regeneration, wound healing, proliferation, and in cell motility [59,60].…”
Section: Discussionmentioning
confidence: 55%
“…The reaction conditions were 95°C for 10 min, followed by 95°C for 10 sec for 40 cycles and 60°C for 60 sec. The relative mRNA expression level of each sample compared with GAPDH expression was derived using the 2 −ΔΔCq method ( 18 , 19 ).…”
Section: Methodsmentioning
confidence: 99%